2021
DOI: 10.1002/jctb.6942
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimization of extractive distillation of benzene–n‐propanol with ionic liquid as entrainer

Abstract: BACKGROUND: The binary benzene-n-propanol azeotrope can be formed in chemical production. Extractive distillation is an important azeotrope separation technology and an ionic liquid is a type of excellent entrainer. Aspen Plus software was used to simulate the extractive distillation process. The separation performance of ionic liquids was evaluated in terms of total annual cost of the extractive distillation process. The separation mechanism of the azeotrope was quantitatively explained using intermolecular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Similarly, Zhang et al 179 minimized the TAC of an IL-based extractive distillation plant by programing a simulated annealing algorithm. In contrast, Li et al 182 and Wei et al 181 optimized the TAC of IL-based extractive distillation processes by adopting a sequential iterative method.…”
Section: Process Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Zhang et al 179 minimized the TAC of an IL-based extractive distillation plant by programing a simulated annealing algorithm. In contrast, Li et al 182 and Wei et al 181 optimized the TAC of IL-based extractive distillation processes by adopting a sequential iterative method.…”
Section: Process Optimizationmentioning
confidence: 99%
“…109,110 Aside from the study of the extractive distillation column's key variables, Kulajanpeng et al 284 completed the flowsheet with a previously optimized configuration scheme comprising a flash distillation unit and a stripping column for solvent regeneration, reducing the flow in the stripping column by exploiting the previous flash distillation. 306 In other studies, a second distillation column, 124,281,282 a flash distillation unit, 42,285,286 a stripping column, 182 two flash units, 292,301 or flash + stripping column + flash 179 were the most extended separation trains used to complete the process. The separation Another option that can be tuned at the process scale is the composition of a hybrid solvent to modulate key process indicators by changing the composition of the mixture, as stated in Section 4.5.…”
Section: Separation Processes By Extractive Distillationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, if the azeotropic point can be eliminated entirely and the relative volatility near the azeotropic point can be expanded, the above problems can be eradicated. As chemical technologies that can eliminate azeotropism and expand relative volatility, azeotropic distillation, pressure swing distillation, and extractive distillation are potentially good candidates. Compared with azeotropic distillation, extractive distillation has a relatively simple process, for the entrainer added will not form a new azeotropic system with the original components.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study of the extractive distillation mechanism is crucial for the selection and molecular design of extractants. Therefore, in order to better separate cyclohexane and ethanol, it is of great significance to describe the separation mechanism of extractants based on QC calculations to select the appropriate extractant. , Based on QC calculations, Feng et al analyzed the possibility and mechanism of an IL as an extractant to separate acetic acid and water from the aspects of molecular configuration, charge density, and interaction energy and selected the best extractant [Bmim]­[BDP]. Woo et al found a new IL extractant for extractive distillation by molecular simulation.…”
Section: Introductionmentioning
confidence: 99%